Perceraian Karena Intervensi Orang Tua Terhadap Rumah Tangga Anak - Ahmad Zuhri Nafi; M. Nur Kholis Al Amin (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2018)
This article describes the analysis of divorce decisions on the grounds of parental intervention to a family of young couples in the Religious Court of Demak regency. The method of data collection is in-depth interviews and documentation, surely as important instruments, so that the subject matter of this research can be revealed properly, both in the process of divorce proceedings and judges' consideration in their decisions. This research, than, suggests one lesson food for thought that in social life within community, parent’s role has an important meaning in the lives of their son’s or daughter’s household in their position as mediator (hakam) and giving advice when conflicts occur in the family of son or daughter. Likewise, married couples must know the limitations and responsibilities of each in relation to their parents, so as to create healthy family relationships without intervention